Effect of fluoride solutions on the shear bond strength of orthodontic brackets - Leódido,Gabriela da Rocha (2012)
The aim of this in vitro study was to evaluate the shear bond strength of brackets after pre-treatment with different fluoride solutions. This study used 48 freshly extracted sound bovine incisors that were randomly assigned to 4 experimental groups (n=12). CG: (control) without treatment; NF: 4 min application of neutral fluoride; APF: application of 1.23% acidulated phosphate fluoride (APF) for 4 min; and SFV: application of 5% sodium fluoride varnish for 6 h. For each group, after surface treatment, prophylaxis of enamel and bracket bonding with Transbond XT composite resin (3M) were performed following the manufacturer's specifications. The shear bond strength was performed with a universal testing machine 24 h after fixing the brackets. The tooth surfaces were analyzed to verify the adhesive remnant index (ARI). Data were analyzed statistically by ANOVA and Tukey's test (α=0.05). There was statistically significant difference among the groups (p<0.0001). CG and NF groups presented significantly higher bond strength than APF and SFV. There was no significant difference between CG and NF or between APF and SFV (p>0.05). The analysis of ARI scores revealed that most failures occurred at the enamel-resin interface. It may be concluded that the pre-treatment of enamel with 1.23% APF and 5% SFV prior to fixing orthodontic brackets reduces shear bond strength values.